The Depiction of Immigration in Samuel Selvon's Selected Short Stories - Pospíšilová, Alena (Univerzita Pardubice, 2017)
This bachelor thesis focuses on depiction of immigration in selected short stories from Ways of Sunlight written by Samuel Selvon. The theoretical part covers postcolonial and West Indian literature, history of immigration from West Indies, and overall Caribbean experience. The analytical part is a comparative study that selects four short stories set in London and examines similarities and differences in how they depict immigrant life.
Vyobrazení přistěhovalectví ve vybraných povídkách Samuela Selvona
Keywords: Samuel Selvon; Cesty světla; přistěhovalectví; rasismus; diaspora; postkoloniální literatura; Samuel Selvon; Ways of Sunlight; immigration; racism; diaspora; postcolonial literature